How to catch Santa - Reagan, Jean; Wildish, Lee (New York Alfred A. Knopf, 2015)
A child provides instructions for properly capturing Santa--briefly--to ask him questions and tell him things.
"A holiday How to ... book!"--Cover.
103124
Keywords: Santa Claus; Christmas stories; Christmas; Fiction; Juvenile works